Blaspheming Across Borders No. 1: The Carnivals of Santana de Parnaíba and Cajamarca and a Brazil and Peru creation (Móin-Móin Magazine - Studies in the Art of Puppetry, 2026)
The text narrates the first stage in the creation of Blasfêmia, a Brazil–Peru coproduction that takes popular and community-based carnival manifestations from both countries as a means to question elements of Latin American identity through festivity and death. Drawing from the carnivals of Santana de Parnaíba (Brazil) and Cajamarca (Peru), the process involved field research, artistic residency, and international circulation, generating reflections on a creation in transit — multicultural and frictional. The article presents the scope of the investigation, the account of the field experience in Cajamarca, and the principles that supported the subsequent movements of creation and circulation.
Keywords: collective creation; latin american theatre; transculturality; carnival; cajamarca